On the Question of Collective Theoretical Work - N. V. Litvak (Vestnik MGIMO-Universiteta)
The article analyzes the modern forms of scientific collaboration - theoretical and scientific seminars. The author accentuates the problem of interaction among scientists and between the scientific community and the society at large, as well as the difficulties of individual and collaborative research and the need for collective theoretical creativity. Possible new forms thereof are suggested.